Neoadjuvant leukocyte interleukin injection immunotherapy improves overall survival in low-risk locally advanced head and neck squamous cell carcinoma –the IT-MATTERS study - Talor, Eyal; Tímár, József; Lavin, Philip; Cipriano, John; Markovic, Dusan; Ladányi, Andrea; Karpenko, Andrey; Bondarenko, Igor; Stosic, Srboljub; Sobat, Hrvoje; Zhukavets, Aliaksandr; Imamovic, Nazim; et al. (Pathology oncology research, 2025)
The randomized controlled pivotal phase 3 study evaluated efficacy and safety of neoadjuvant complex biologic, Leukocyte Interleukin Injection (LI), administered for 3 consecutive weeks pre-surgery, in treatment naïve resectable locally advanced primary squamous cell carcinoma of oral cavity and soft palate. Randomization 3:1:3 to LI+/-CIZ (cyclophosphamide, indomethacin, and zinc)+SOC, or SOC (standard of care) alone. LI-treated patients received 400 IU (as interleukin-2 equivalent; 200 IU peritumorally, 200 IU perilymphatically) sequentially, daily 5 days/week for 3 weeks before surgery. All subjects were to receive SOC. Post-surgery, patients with low risk for recurrence were to receive radiotherapy, while those with high risk received concurrent chemoradiotherapy. Median follow-up was 56 months. There were 923 ITT (Intent-to-Treat) subjects (380 ITT low-risk and 467 ITT high-risk). Pre-surgery objective early response (45 objective early responders; 5 complete responses [CRs], 40 partial responses [PRs], confirmed by pathology at surgery. LI (+/− CIZ) had 8.5% objective early responders (45/529 ITT) and 16% objective early responders (34/212 ITT low-risk) vs. no reported SOC objective early responders (0/394 ITT). Objective early responders significantly lowered death rate to 22.2% (ITT LI-treated), 12.5% (ITT low-risk LI + CIZ + SOC), while the ITT low-risk SOC death rate was 48.7%. Thus, objective early response impacted overall survival (OS); proportional hazard ratios were 0.348 (95% CI: 0.152–0.801) for ITT low-risk LI-treated, 0.246 (95% CI: 0.077–0.787) for ITT low-risk LI + CIZ + SOC. ITT low-risk LI + CIZ + SOC demonstrated significant OS advantage vs. ITT low-risk SOC (unstratified log-rank p = 0.048; Cox hazard ratio = 0.68; 95% CI: 0.48–0.95, Wald p = 0.024 [controlling for tumor stage, tumor location, and geographic region]). Absolute OS advantage increased over time for ITT low-risk (LI + CIZ + SOC)-treated vs. ITT low-risk SOC: reaching 14.1% (62.7% vs. 48.6%) at 60 months, with 46.5 months median OS advantage (101.7 months vs. 55.2 months), respectively. Quality of life benefit for complete responders sustained for >3 years post LI treatment. Percent treatment-emergent adverse events were comparable among all treated groups. No excess safety issues were reported for LI over SOC alone post-surgery. NCT01265849, EUDRA:2010-019952-35.